Factors affecting physician decision-making regarding antiplatelet therapy in minor ischemic stroke - Liu, Tingting; Li, Yanan; Niu, Xiaoyuan; Wang, Yongle; Zhang, Kaili; Fan, Haimei; Ren, Jing; Li, Juan; Fang, Yalan; Li, Xinyi; Wu, Xuemei (Frontiers in Neurology, 2022)
Purpose To identify the most important factors affecting physician decision-making regarding antiplatelet therapy. Methods We retrospectively gathered data from minor ischemic stroke patients with NIHSS scores ≤ 5 within 72 h of onset from 2010 to 2018. The population was divided into four groups by initial antiplatelet therapy: aspirin monotherapy (AM), dual antiplatelet therapy with aspirin and a loading dose of clopidogrel (clopidogrel loading dose of 300 mg on the first day; DAPT-ALC), dual antiplatelet therapy with aspirin and no loading dose of clopidogrel (clopidogrel 75 mg daily, no loading dose; DAPT-AUC), and clopidogrel monotherapy (CM). Results In total, 1,377 patients were included in the analysis (excluding patients who accepted thrombolytic drugs, participated in other clinical trials, or had not used antiplatelet drugs). The mean ± S.D. age was 62.0 ± 12.7 years; 973 (70.7%) patients were male. The four groups were AM (n = 541, 39.3%), DAPT-ALC (n = 474, 34.4%), DAPT- AUC (n = 301, 21.9%), and CM (n = 61, 4.4%). Patients receiving antiplatelet monotherapy were older than those receiving dual antiplatelet therapy (63.7–65.7 vs. 59.6–61.4 years), and the median initial systolic blood pressure level was higher in the DAPT-ALC group than in the other groups (all P < 0.05). Patients under 75 years old with an admission SBP lower than 180 mmHg, a history of AM, coronary heart disease, no history of intracerebral hemorrhage, stroke onset occurring after guideline recommendations were updated (the year of 2015), onset-to-arrival time within 24 h, and initial NIHSS score ≤ 3 were more likely to take DAPT-ALC than AM. Compared with DAPT-ALC, DAPT-AUC was associated with an initial SBP level lower than 180 mmHg, a history of smoking, hypertension, no history of ICH, previous treatment with antihypertensives, and onset year after the recommendations were updated. Conclusions Many factors affect doctors' decisions regarding antiplatelet therapy, especially guidelines, age, admission SBP level, and hypertensive disease.